Delivery mode and maternal gestational diabetes are important factors in shaping the neonatal initial gut microbiota - Shi, Xuan; Liu, Yanfang; Ma, Teng; Jin, Hao; Zhao, Feiyan (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundThe infant gut microbiome’s establishment is pivotal for health and immune development. Understanding it unveils insights into growth, development, and maternal microbial interactions. Research often emphasizes gut bacteria, neglecting the phageome.MethodsTo investigate the influence of geographic or maternal factors (mode of delivery, mode of breastfeeding, gestational diabetes mellitus) on the gut microbiota and phages of newborns, we collected fecal samples from 34 pairs of mothers and their infants within 24 hours of delivery from three regions (9 pairs from Enshi, 7 pairs from Hohhot, and 18 pairs from Hulunbuir) using sterile containers. Gut microbiota analysis by Shotgun sequencing was subsequently performed.ResultsOur results showed that geographic location affects maternal gut microbiology (P < 0.05), while the effect on infant gut microbiology was not significant (P = 0.184). Among the maternal factors, mode of delivery had a significant (P < 0.05) effect on the newborn. Specific bacteria (e.g., Bacteroides, Escherichia spp., Phocaeicola vulgatus, Escherichia coli, Staphylococcus hominis, Veillonella spp.), predicted active metabolites, and bacteriophage vOTUs varied with delivery mode. Phocaeicola vulgatus significantly correlated with some metabolites and bacteriophages in the early infant gut (P < 0.05). In the GD group, a strong negative correlation of phage diversity between mother and infants was observed (R = -0.58, P=0.04).ConclusionIn conclusion, neonatal early gut microbiome (including bacteria and bacteriophages) colonization is profoundly affected by the mode of delivery, and maternal gestational diabetes mellitus. The key bacteria may interact with bacteriophages to influence the levels of specific metabolites. Our study provides new evidence for the study of the infant microbiome, fills a gap in the analysis of the infant gut microbiota regarding the virome, and emphasizes the importance of maternal health for the infant initial gut virome.